Socio-psychological adaptation in the context of the trend of transition to a remote work format - A. A. Avdeeva; M. V. Iontseva (Вестник университета)
Digital technologies have become firmly embedded in all spheres of our life. Presently, it is almost impossible to imagine a single day without the use of gadgets and electronic devices. An important place in the modern world is occupied by the problem of socio-psychological adaptation, which takes place in the process of digitalization. Managers pay attention to the adaptation process of new employees, but they do not always take into account that the transition to a remote format of work for most employees can cause a stressful state. Therefore, it is so important to organize comfortable conditions during the adaptation period to new working conditions. The article considers the socio-psychological features that allow them to pass most effectively the adaptation period in the conditions of the tendency to switch to a remote format of work. The most distinctive characteristics are highlighted, in which the adaptation is as successful as possible.